Development of heat dissipation multilayer media for magnetic hologram memory. Issue 7 (14th May 2020) - Nakamura, Yuichi; Lim, Pang Boey; Goto, Taichi; Uchida, Hironaga; Inoue, Mitsuteru
Abstract: Holographic memory is a strong candidate for next‐generation optical storage with high recording densities and data transfer rates, and magnetic hologram memory using a magnetic garnet, as the recording material, is expected to be used as a rewritable and stable storage technology. We succeeded in recording and reconstruction of two‐dimensional data in magnetic hologram without error. However, the diffraction efficiency is insufficiently high for actual storage devices. To increase the diffraction efficiency, it is important to record deep magnetic fringes, whereas the merging of fringes due to the excess heat near the medium surface generated during the thermomagnetic recording process must be suppressed. To avoid this merge of fringes, we proposed a multilayered structure in which the magnetic layers are divided by the transparent heat dissipation layers (HDL) to control the heat diffusion. In this study, we propose a simple thermal design method for designing the HDL multilayer structure. Using this model, we designed and fabricated an HDL multilayer medium in which the recording magnetic layers are discrete in the film. The HDL multilayer medium exhibited diffraction efficiency higher than that of the single‐layer medium, and error‐free recording and reconstruction were achieved using the magnetic assist technique.